2015
DOI: 10.1093/sysbio/syv084
|View full text |Cite
|
Sign up to set email alerts
|

The Phylogeny ofRickettsiaUsing Different Evolutionary Signatures: How Tree-Like is Bacterial Evolution?

Abstract: Rickettsia is a genus of intracellular bacteria whose hosts and transmission strategies are both impressively diverse, and this is reflected in a highly dynamic genome. Some previous studies have described the evolutionary history of Rickettsia as non-tree-like, due to incongruity between phylogenetic reconstructions using different portions of the genome. Here, we reconstruct the Rickettsia phylogeny using whole-genome data, including two new genomes from previously unsampled host groups. We find that a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 94 publications
3
65
0
Order By: Relevance
“…Support values are based on 100 rapid bootstrap replicates. Major Rickettsia groups have been collapsed for visualisation purposes and names are according to (Murray et al, 2016). Numbers in parenthesis represent the number of genomes used for the analysis (Table S2).…”
Section: Genome Contentmentioning
confidence: 99%
“…Support values are based on 100 rapid bootstrap replicates. Major Rickettsia groups have been collapsed for visualisation purposes and names are according to (Murray et al, 2016). Numbers in parenthesis represent the number of genomes used for the analysis (Table S2).…”
Section: Genome Contentmentioning
confidence: 99%
“…Rickettsia conorii , R. rickettsii and R. japonica , the causative agents of Mediterranean, Rocky Mountain, and Japanese spotted fever, respectively, that are transmitted by ixodid ticks); (ii) the typhus group (TGR) (e.g. R. typhi , the causative agent of murine typhus transmitted by fleas, and R. prowazekii , the causative agent of epidemic typhus transmitted by the body louse); (iii) the transitional group (TRGR) transmitted by fleas, mites and ticks; (iv) the R. bellii group (ticks); (v) the R. canadensis group; (vi) the Helvetica group; (vii) the Scapularis group; (viii) the Adalia group; and (ix) the Hydra group [14]. …”
Section: Introductionmentioning
confidence: 99%
“…R. bellii has been reported as the species of Rickettsia most commonly infecting ticks in Brazil (Krawczak et al, 2018;Labruna et al, 2011). This bacteria belongs to a rickettsial basal group that includes a variety of closely related agents infecting leeches, insects, protozoa, or even plants (Murray et al, 2016;Weinert et al, 2009), making it possible that these other organisms could be related to the seropositivity of R. bellii in the present study, a condition still not investigated. Medeiros et al (2013) demonstrated the occurrence of cross-reaction between different species of Rickettsia in horses.…”
Section: Discussionmentioning
confidence: 82%